Wealth elites in Delhi-NCR - Thampi, Anjana; Anand, Ishan (Southern Centre for Inequality Studies (SCIS), 2023)
Delhi-National Capital Region (NCR) is an ever-expanding inter-state planning region that has occupied an important place in the history of the South Asian sub-continent. Wealth inequality is the highest in this region of the country, as per large-scale household sample surveys. We study the evolution of wealth in this region using secondary data, primary data collection, and detailed interviews. Our interviews of key informants and case studies of wealthy elites revealed five key themes: real estate, land, and farmhouses; caste and community networks; start-ups; politics and wealth creation; and investment in educational institutions. Our interviews revealed that there were three categories of elites who derived their wealth from land in Delhi NCR: land with traditional business families; the ‘babu-brigade’ that includes the bureaucrats and professionals who bought government land for a pittance between the 1960s and the 1980s; and traditional agricultural communities. Our analysis of the trajectory of wealth accumulation of elites over time reveals certain key themes and processes that have enabled the reproduction, expansion, or shrinking of wealth.
Keywords: Wealth Inequality; Delhi-National Capital Region (NCR); Real estate, land, and farmhouses; Caste and community networks; Start-ups; Politics and wealth creation; Investment in educational institutions